Socialization Of The Use Of Chatgpt In Academics In Improving The Quality Of Research Lecturers In Indonesia: Pengabdian - Ifah Masrifah; Muhammad Rifai; Vinno P. Manoppo; Rabith Madah Khulaili Harsya; Rahmawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The socialization activity of the use of ChatGPT for lecturers was carried out on Wednesday, February 19, 2025 in Bekasi, West Java, Marantha Christian University Bandung, and Maulana Malik Ibrahim State Islamic University Malang. The result in this article show the socialization of the use of ChatGPT for lecturers that have been carried out, it shows that lecturers are educated and able to understand the need for ChatGPT in improving the quality of research. The socialization carried out explains how the use of ChatGPT supports lecturers in the research process. This activity contributes to improving the quality of research in Indonesia by empowering lecturers to maximize the use of ChatGPT amidst the rapid development of AI. In improving the quality of lecturers' research, ChatGPT is used to quickly search for information related to research and validate research accurately, as well as the potential of ChatGPT in facilitating and supporting research. Lecturers are intelligent human resources who are able to use technology wisely. Therefore, activities such as the socialization of ChatGPT for lecturers are very necessary.